Pengaruh Kuat Geser Matos dan Semen Terhadap Tanah Ekspansif - Nikodemus Budi Prayitno; Daniel Hartanto; Djoko Suwarno (G-SMART, 2018)
The development of development in Indonesia is very advanced and requires extensive land to build. A lot of development has been carried out to increase the pace of development but has faced several obstacles. The constraints faced are often land conditions that do not support. One of the soil conditions is expansive soil. This expansive soil condition must be corrected so as not to damage the building built on the land. One way to improve this is to add additional ingredients to improve the expansive soil. The added ingredients used are matos and cement.This research is also useful to determine expansive soil shear strength with the addition of matos and cement. The method of mixing matos is using cement and water. If the matos are not mixed with cement, the results obtained cannot be maximized. When it is mixed homogeneously the expansive soil experiences better mixing than without the addition of matos and cement. Shear strength also increased significantly when mixed with matos and cement.